Histology of juvenile skin of Lepidosiren paradoxa Fitzinger, 1837 (Sarcopterygii, Dipnoi) - ROMANO,LUIS ALBERTO (2019)
Abstract: The skin of three juvenile Lepidosiren paradoxa specimens was examined. The epidermis was composed of a polystratified epithelium resting on a basement membrane, including mucus-secreting cells, and a cuticle of mucopolysaccharides on the surface. Two types of skin receptors, electroreceptors and mechanoreceptors, were found; the first type was located in the dermoepidermal junction, and the second type was completely intraepiderma. The skin structure of these fish, suggests the possibility of the skin participating in the breath.